1998
DOI: 10.1016/s0022-5347(01)62928-8
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Following Retropubic Prostatectomy: Simple Digital Rectal Pressure Could Be Lifesaving

Abstract: Simple digital rectal pressure is a safe, effective and logical method of controlling venous bleeding from the dorsal venous or other plexus between the rectum and symphysis pubis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Bleeding following open prostatectomy is still the most common early surgical complication [10]. Hedican and Walsh [11] found that mechanical factors, such as nonligated or poorly ligated vessels, are an uncommon cause of bleeding postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding following open prostatectomy is still the most common early surgical complication [10]. Hedican and Walsh [11] found that mechanical factors, such as nonligated or poorly ligated vessels, are an uncommon cause of bleeding postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvements in the technique for RRP have improved outcomes dramatically, blood loss during RRP is still a major concern because of the prostate's rich venous supply . The impact of significant intraoperative blood loss on the patient's outcome is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Although improvements in the technique for RRP have improved outcomes dramatically, blood loss during RRP is still a major concern because of the prostate's rich venous supply. 1,2 The impact of significant intraoperative blood loss on the patient's outcome is multifactorial. Patients with lower postoperative hemoglobin after orthopedic and colorectal surgeries have been associated with prolonged hospitalization, 3,4 and in RRP lower blood loss has been associated with better short-term and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We combined the idea of a pressure-controlled balloon used in the Sengstaken tube, and the pressure applied on the prostate blood supply from the rectum, described by Kirollos [10] and modified by Osman et al [11] . We then developed our new technique (RB), with a measured pressure in the rectum to avoid pressure necrosis on the rectal wall, to facilitate haemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques are capsular plication either longitudinal or transverse, packing the prostatic fossa with gauze or by an inflated catheter balloon, early vascular control before cystotomy, and transurethral endoscopic coagulation by a second surgical team [8,9] . Kirollos [10] reported that life-threatening bleeding after prostatectomy (the patient received 12 units of blood) was controlled only by anterior digital rectal pressure for 10 min. Thereafter, Osman et al [11] used a gauze pack inserted into the patient’s rectum opposing the prostate, after TVP.…”
Section: Introductionmentioning
confidence: 99%